RESEPTIVE AND EXPRESSIVE LANGUAGE ABILITY OF BILINGUAL CHILD WITH ADHD: A Case Study at SDS Permata Ananda Bekasi. - Marita, Tia; Sastra, Gusdi; Lindawati, Lindawati (TELL - US JOURNAL, 2020)
This research focused on examining the receptive and expressive abilities of a child with ASD/ADHD with initial name “T” who is able to communicate with two language or a bilingual at SDS Permata Ananda in Bekasi. ASD is the condition of a child with developmental disorder mostly affects the ability in interaction, communication, and socializing. The purpose of this research is to find out the receptive and expressive ability of a child with such difficulties and able to acquire not one but two language in young age. This research was conducted by using observation method and Simak, Libat, Cakap (SLB) technique in which researchers were directly involved in interviews and interactions with the subject. The language used in interactions is Indonesian as T’s first language (L1) and English as her second language (L2). The results of this study indicated that the subject has excellent receptive and expressive abilities in receiving and producing speech both in L1 and L2. The receptive and expressive ability of the subject both in L1 and L2 can be found from how the subject is able to understand the meaning and purpose of the speech of the interlocutor and then provided responses in the form of speech that is appropriate to the context of the speech of the interlocutor. These findings prove that by getting the right treatments and strategies as early as possible, the interaction difficulty will not become a problem in language acquisition.